Angiotensin converting enzyme inhibitor-induced hepatotoxicity: two case reports and review of literature - Nadir YÖNETCİ and Mehmet İŞLER and Serhat BOR and Sedat ERTEM and A. Ömer ÖZÜTEMİZ and Galip ERSÖZ and Hakan YÜCEYAR and Yücel BATUR and Galip ERSÖZ and Hanefi ÇAVUŞOĞLU and et al. (Turkish Journal of Gastroenterology, 2020)
-